Criminal Psychology : nature, nurture, culture : a textbook and practical reference guide for students and working professionals in the fields of law enforcement, criminal justice, mental health, and forensic psychology - Miller, Laurence (Springfield, Ill. : Charles C. Thomas, 2012)
"Criminal psychology is the application of the principles of normal and abnormal psychology to the understanding, prediction, and control of criminal behavior. 'Criminal Psychology: Nature, Nurture, Culture' provides an in-depth yet readable introduction to the foundations of criminal psychology as it is understood and practiced from the classroom to the courtroom. The book is organized into five sections.Part I - The Nature and Origins of Criminal Behavior; Part II - Personality, Psychopathology and Crime; Part III - The Homicides; Part IV - Sex Crimes and Family Crimes; Part V - Other Crimes and Punishments." -- back cover
Includes bibliographical references (p. 589-764) and index.
Keywords: Criminal psychology; Criminal psychology -- Textbooks; Criminal psychology -- United States